Assessing Industry Concentration: The Case of Aluminum - Litvak, Isaih A.; Maule, Christoper J. (Journal of International Business Studies, 1984)
The article examines the use and measurement of certain concepts from the literature of industrial organization when applied to the study of international industries. It is argued that considerable care needs to be taken in defining markets and in evaluating information concerning concentration. This issue is examined in the context of the international bauxite-aluminum industry. The factors leading to overstating and understating levels of concentration are discussed.